What are the information needs of parents caring for a child with Glutaric aciduria type 1? - Hilary Piercy; Mildrid Yeo; Sufin Yap; Anthony R. Hart (BMC, 2019)
Abstract Background Newborn screening has enabled the early diagnosis of Glutaric aciduria type 1, with the possibility of improving neurological outcomes in affected children. Achieving those outcomes requires parents to effectively manage their child's condition by adherence to a strict dietary regime and responding to situations that may trigger decompensation. The specific information and support needs of this group of parents are unknown. Methods A focus group with five parents was conducted to gain insights into the information that parents needed and the ways in which they accessed and used information to manage their child's condition. A topic guide was used to direct the discussion which was recorded and fully transcribed. All participants gave informed consent. Data were analysed using thematic analysis, a structured approach that contributes to transparency and validity of results while allowing the integration of predetermined and emerging themes. To ensure rigour, two researchers were involved in initial coding of data and key analytic decisions. Results Two main themes were identified. 'Understanding the condition' explored parent's needs to understand the scientific complexity of the condition and to be aware of the worst case scenario associated with loss of metabolic control. 'Managing the condition' explained how parents co-ordinated and controlled the involvement of other carers and parents' need to be active partners in medical management to feel in control of the situation. Conclusions The study highlights the importance of addressing parents' initial and ongoing informational needs so they can fulfil their role and protect their child from metabolic harm.